Reputation as a Benefitanda Burden? How Stakeholders’ Organizational Identification Affects the Role of Reputation Following a Negative Event - Zavyalova, Anastasiya; Pfarrer, Michael D.; Reger, Rhonda K.; Hubbard, Timothy D. (Academy of Management Journal, 2016)
Research about the effects of an organization’s general reputation following a negative event remains equivocal: Some studies have found that high reputation is a benefit because of the stock of social capital and goodwill it generates; others have found it to be a burden because of the greater stakeholder attention and violation of expectations associated with a negative event. We theorize that stakeholders’ level of organizational identification helps explain which mechanisms are more dominant. We test our hypotheses on a sample of legislative references associated with National Collegiate Athletic Association major infractions from 1999–2009. Our results indicate that high reputation is a burden for an organization when considering low-identification stakeholder support: As the number of legislative references increases, a high-reputation university will receive fewer donations from non-alumni donors compared to universities without this asset. In contrast, high reputation is a benefit when considering high-identification stakeholder support: As the number of legislative references increases, a high-reputation university will receive more donations from alumni donors compared to universities without this asset. However, an exploratory investigation reveals that alumni donations to high-reputation universities decline as the number of legislative references increases, suggesting that the benefit of a high reputation has a limit.